Ship ahoy - Beheim, Eric
"Ship Ahoy" (1928) is a unique record of the conditions and traditions of the North American lumber trade featuring an unidentified schooner equipped with a fore and aft rig as it transports lumber from the Carolinas up the coast to a northern port. Music by Eric Beheim. [Cover]
10 Min., s/w., stumm
Orig.: USA 1928